Humanities for medical students - Alexeenko, Alla; Martynenko, Nataliia (My University, 2014)
The article dwells upon the philosophy of humanitarian education and culture of health, which plays an important role in the formation of the student’s personality. The authors of the article substantiate the necessity of some educational courses for the students of medical schools, such as “Ethic” and “Ethical Problems of Medicine”, “Spirituality and Health”, “Culture of Health”, etc. The knowledge gained on these courses can be used by the students during their sanitary-educational practices – in their work with the population, for the formation of basic skills of healthy lifestyle against incurable diseases.
Keywords: philosophy of health; humanitarian training; spirituality and health; culture of health; ethical problems of medicine